Analysis of the Implementation of Priority Services of the Ministry of ATR/BPN as an Effort to Modernize Land Services (Study at the Bungo Regency Land Office) - Novi Ardiansyah; Dwi Putranto Riau; Tukiyat (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Land service modernization is an important part of bureaucratic reform aimed at improving the quality of digital-based public services. This study aims to analyze the level of service importance and performance, map the strategic position of services using Importance–Performance Analysis (IPA), and identify the dominant factors influencing public satisfaction with the implementation of 7 priority services of the Ministry of ATR/BPN at the Bungo Regency Land Office. The study used a quantitative approach with a survey method of 100 respondents selected using purposive sampling. Data analysis was conducted using descriptive statistics, IPA, and multiple linear regression. The results showed that most service attributes were in the fair to good category. The IPA results indicated that technology utilization was a top priority for improvement (Quadrant I), while transparency, service speed, and officer professionalism were in Quadrant II (maintained). The regression results indicated that transparency, service speed, officer professionalism, and ease of procedures had a significant influence on public satisfaction. This study recommends strengthening digitalization strategies, improving human resource competencies, and optimizing electronic-based service systems.